Analisa Ekspor Minyak Kelapa Sawit Indonesia dan Isu Pembatasan Penggunaan Produk Minyak Kelapa Sawit oleh Uni Eropa - Affan Hanif Imaduddin; Lucky Nugroho; Dian Sugiarti (Universitas 45 Surabaya, 2023)
The purpose of this study is to analyze the influence of Leader Member Exchange (LMX) and Team Member Exchange (TMX) on employee performance through job satisfaction at the Population and Civil Registration Office in North Maluku. The sampling technique uses saturated samples (census) with a total sample of 112 respondents at the Provincial Population and Civil Registration Office in Maluku. The data analysis used in this study used SmartPLS Partial Least Square. The results of data analysis in this study show that 1) Leader Member Exchange (LMX) has a positive and significant effect on Job Satisfaction. 2) Excange Team Member has a positive and significant effect on job satisfaction. 3) Leader Member Exchange has a positive and significant effect on employee performance. 4) Team Member Exchange (TMX) has no effect on employee performance. 5) Job satisfaction has a positive and significant effect on employee performance. 6) Leader Member Exchange has a positive and significant effect on employee performance through job satisfaction. 7) Team Member Exchange has a positive and significant effect on employee performance through job satisfaction.